Triterpenes from the fruits of Rosa laevigata with acetylcholinesterase and Aβ-aggregation inhibitory activities. Issue 3 (4th January 2016) - Gao, Pin-Yi; Wang, Meng; Liu, Xue-Gui; Gao, Yi-Xing; Li, Jia-Luo; Zhang, Zhen-Xue; Lin, Hou-Wen; Song, Shao-Jiang
Abstract : A lupane-type triterpene (1 ) featuring a rare 2-hemiacetal moiety and aromatic ester derivatives (2–6 ) were isolated from R. laevigata and evaluated to possess acetylcholinesterase and Aβ-aggregation inhibitory activities. Abstract : A lupane-type triterpene (1 ) featuring a rare 2-hemiacetal moiety in its A ring and aromatic ester derivatives (2–6 ) were isolated from the fruits of R. laevigata and evaluated to possess acetylcholinesterase and Aβ-aggregation inhibitory activities. Their structures were determined by multi-spectroscopic methods, chemosynthesis and CD analysis.